“In-situ” antimony film electrode for the determination of tetracyclines in Argentinean honey samples - Krepper, Gabriela (2017)
The main goal of this work is the application of an antimony film electrode (SbFE) prepared for the first time “in-situ” to determine organic compound as tetracyclines commonly used in Argentine for hive treatment. The SbFE was prepared on a glassy carbon electrode (GCE) and square wave cathodic stripping voltammetry (SWCSV) technique was used. The SWCSV parameters were optimized based on a Draper Lin small composite design. The SWCSV response was linear in the TCs concentration range from 0.40 to 3.00 μM with a limit of detection (LOD) of 0.15 μM. The proposed method is a good and simple alternative to the determination of tetracyclines in Argentinean honeys samples. Recovery experiments were performed using spiked honey samples with standard deviation values from 0.75% and 9.69%.